2007
DOI: 10.1128/jcm.02510-06
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Distribution of Invasive Neisseria meningitidis Serogroup C Strains Circulating from 1976 to 2005 in Greater São Paulo, Brazil

Abstract: Meningococcal disease is characterized by cyclic fluctuations in incidence, serogroup distribution, and antigenic profiles. In greater São Paulo, Brazil, there has been a constant increase in the incidence of serogroup C meningococcal disease since the late 1980s. To gain an understanding of changes in serogroup C meningococcal disease over three decades in greater São Paulo, Brazil, 1,059 invasive Neisseria meningitidis serogroup C isolates from 1976 and 2005 were analyzed. Three major clone complexes, sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 46 publications
1
42
0
5
Order By: Relevance
“…in educational institutions, military barracks, or other crowded, semi-closed places. (Bijlsma et al, 2014;Brehony et al, 2007;Chacon-Cruz et al, 2014;Deghmane et al, 2010;de Lemos et al, 2007;ECDC, 2013;Fazio et al, 2009;Garnier et al, 2011;Simon et al, 2013). Also in Poland between 2006-2009 several outbreaks were recorded as well as an increase of incidence of MenC ST-11CC (Fig.…”
Section: St-11ccmentioning
confidence: 99%
“…in educational institutions, military barracks, or other crowded, semi-closed places. (Bijlsma et al, 2014;Brehony et al, 2007;Chacon-Cruz et al, 2014;Deghmane et al, 2010;de Lemos et al, 2007;ECDC, 2013;Fazio et al, 2009;Garnier et al, 2011;Simon et al, 2013). Also in Poland between 2006-2009 several outbreaks were recorded as well as an increase of incidence of MenC ST-11CC (Fig.…”
Section: St-11ccmentioning
confidence: 99%
“…These were previously found in other states of Brazil, but not in RS. 2,24,25 These hypervirulent clones have been reported to cause outbreaks and epidemics worldwide, reinforcing the importance of molecular characterization of MD cases in order to monitor the spread of these lineages and to establish control measures for the disease. 26e28 There was a higher genetic diversity in isolates within the ST-32 complex than was seen between 1995 and 2003, with 18 different STs, 8 of them novel.…”
Section: Discussionmentioning
confidence: 96%
“…Serogroup C:P1.14-6 was the most prevalent serosubtype in greater São Paulo in a study reporting an increase of this phenotype in the last few years. 25 Sequencing of some of these isolates from São Paulo revealed that they have the genotype P1.22,14-6 (A.P. Lemos, personal communication), the same as RS strains.…”
Section: Discussionmentioning
confidence: 96%
“…31,53 In Rio de Janeiro, the cluster A4 epidemic strains often express sero-subtype 2b:P1.10 ( Figure 3), which has caused epidemic and hiperendemic waves of disease in other parts of Brazil but expressing an unusual subtype, P1.3. 2,11,12 Serogroup C disease has emerged in the Rio de Janeiro metropolitan area once more after the year 2000, and now it represents more than 90% of the clinical isolates ( Figure 1). The strains have mainly been associated with the phenotypes C:23:P1.14-6, C:4,7:P1.19,15, P1.7.…”
Section: Discussionmentioning
confidence: 99%
“…1 The epidemic strain was characterized as phenotype 2a:P1.5, 1.2 genetically related to the ET-37 complex. 2 In the 1980s, 1408 cases of meningococcal disease were reported, with incidence of 1-5 cases/\100,000/\ year (Rio de Janeiro City Health Department). Since 1985, a steady increase of serogroup B clinical isolates was observed, initially attributed to an improvement in the laboratory diagnostic procedures in identifying meningeal pathogens ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%